2012
DOI: 10.1104/pp.111.189860
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes Underlying an Iron Efficiency Quantitative Trait Locus in Soybean

Abstract: Prevalent on calcareous soils in the United States and abroad, iron deficiency is among the most common and severe nutritional stresses in plants. In soybean (Glycine max) commercial plantings, the identification and use of iron-efficient genotypes has proven to be the best form of managing this soil-related plant stress. Previous studies conducted in soybean identified a significant iron efficiency quantitative trait locus (QTL) explaining more than 70% of the phenotypic variation for the trait. In this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 48 publications
(63 reference statements)
2
102
0
Order By: Relevance
“…By comparing the sequences of the molecular markers used in these studies to the introgressed regions, only the QTL identified on chromosome 3 [47–49] corresponded to an introgressed region (data not shown). Five DEGs corresponded to the region on chromosome 3 [14]. In six hour leaves we identified a S-adenosyl-L-methionine-dependent methyltransferases superfamily protein (Glyma03g28490).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the sequences of the molecular markers used in these studies to the introgressed regions, only the QTL identified on chromosome 3 [47–49] corresponded to an introgressed region (data not shown). Five DEGs corresponded to the region on chromosome 3 [14]. In six hour leaves we identified a S-adenosyl-L-methionine-dependent methyltransferases superfamily protein (Glyma03g28490).…”
Section: Resultsmentioning
confidence: 99%
“…Such a scenario might explain why Bur-0 requires lower levels of IRT1 transcripts when grown on standard growth medium [69] (Table 1). Studies exploiting natural variation have already provided important knowledge about Fe uptake and homeostasis [70,71] and are likely to remain an important research strategy in the future. In summary, the expression of IRT1 requires more than just the core strategy I transcriptional regulators, which may explain the strong connection between Fe uptake and other stress responses [72][73][74][75] and its integration into the plant developmental program [76][77][78].…”
Section: Protein Network Regulating Fe-dependent Transcriptionmentioning
confidence: 99%
“…Although calcareous growth conditions generally reduce the productivity of strategy I plants, there are large differences among strategy I species and genotypes in their tolerance to Fe deficiencyinduced chlorosis. To a certain extent, these differences may relate to sequence deviations in FIT-and bHLHtype transcription factors that are primarily thought to drive IRT1-and FRO2-dependent Fe uptake (Peiffer et al, 2012). However, to date, it still remains unknown how nongraminaceous plants access ferric Fe in the rhizosphere and overcome the problem of low Fe solubility and impeded Fe reducibility in high pH soils.…”
mentioning
confidence: 99%